'Correctness' as the Proper Standard of Review Applicable to 'True' Questions of Jurisdiction in the Set-Aside of Treaty-Based Investor-State Awards. (16th October 2013) - Lévesque, Céline
Abstract: Recent national court decisions have taken a strong stance in favour of the standard of 'correctness' for the review of questions of jurisdiction arising under international investment agreements (IIAs). The application of this standard requires courts to answer a fundamental question: What is the scope of jurisdictional issues under IIAs? It requires them to consider anew issues of consent, not limiting themselves to the intention of 'contract' parties as in international commercial arbitration. The standard of 'correctness' (or de novo review), however, has not been uniformly adopted or applied and it raises a number of objections, some that have merit but many that do not. The first part of the article uses Canadian courts decisions as a case study of the difficulties facing domestic judiciaries in the review of awards rendered under IIAs. Canada serves as a good 'spring board' to the analysis that follows, as five NAFTA Chapter 11 awards have been reviewed by such courts often applying different standards of review. Emphasis is placed on the 2011 decision of the Ontario Court of Appeal in the Cargill v Mexico case which embraced 'correctness' as the proper standard of review for 'true' questions of jurisdiction. Taking into account recent developments in Europe as well as the United States (including the ongoing proceedings regarding BG Group v Argentina ), the second part of the article discusses arguments against correctness and assesses their relative merit. The difficulty in distinguishing between jurisdiction and admissibility and the limited expertise of domestic court judges in treaty interpretation are identified as key challenges for domestic court review of treaty-based investor-State awards under a standard of 'correctness'.